2022
DOI: 10.1111/aji.13557
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation‐related immune proteins in maternal plasma as potential predictive biomarkers for rescue cerclage outcome in women with cervical insufficiency

Abstract: Problem This study aimed to determine whether various novel plasma mediators of immune regulation associated with inflammation could independently predict the clinical outcome of rescue cerclage in patients with cervical insufficiency (CI). Method of study A total of 41 singleton pregnant women (17–25 weeks) who underwent rescue cerclage for CI were retrospectively evaluated. Stored plasma samples were assayed for IGFBP‐1, ‐2, ‐3, IL‐6, latexin, LBP, lipocalin‐2, M‐CSF, MIP‐1α, MMP‐8, ‐9, pentraxin 3, resistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Kim et al [ 9 ] reported AUC values of .686, .691, and .693 for maternal plasma insulin-like growth factor binding protein-3 (IGFBP-3), macrophage inflammatory protein-1 alpha (MIP-1α), and S100A8/A9, respectively, for predicting spontaneous preterm birth of <28 weeks after rescue cerclage; therefore, IGFBP-3, MIP-1α, and S100A8/A9 were considered noninvasive independent biomarkers. However, IGFBP-3, MIP-1α, and S100A8/A9 detection tests, which are limited to laboratories, are not easily accessible for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [ 9 ] reported AUC values of .686, .691, and .693 for maternal plasma insulin-like growth factor binding protein-3 (IGFBP-3), macrophage inflammatory protein-1 alpha (MIP-1α), and S100A8/A9, respectively, for predicting spontaneous preterm birth of <28 weeks after rescue cerclage; therefore, IGFBP-3, MIP-1α, and S100A8/A9 were considered noninvasive independent biomarkers. However, IGFBP-3, MIP-1α, and S100A8/A9 detection tests, which are limited to laboratories, are not easily accessible for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of pro-inflammatory mediators, such as matrix metalloproteinases-8 (MMP-8), interleukin-8 (IL-8), and heat shock protein 70 (Hsp70), in the vaginal fluid have been associated with cervical shortening [38,39]. Maternal plasmatic levels of IL-8 and Hsp70 have also been implicated in the pathogenesis of preterm birth [40][41][42]. However, the plasma levels of Hsp-70 and IL-8 have not been studied in pregnant women with short cervical length.…”
Section: Introductionmentioning
confidence: 99%